IN SEARCH OF A CONFESSIONAL COMPROMISE INTHE“RELIGION-SOCIETY-THESTATE” CONTEXT - KHUSNUTDINOVA, Layla; ISTAMGALIN, Ramil; EFIMENKO, Evgeniy; SADYKOVA, Liana (CENTRAL ASIA AND THE CAUCASUS, 2018)
To suppress the worst forms of religious intolerance, the ideas and constructive potential of tolerance and peace need the public support of the constitutional principles of freedom of conscience and religion within the “religion-society-state” context. Today, the so-called ideological platform of nationalist forces, taking shape within extremist and terrorist international organizations, is inspired by the idea of administrative and territorial changes in Russia’s regions and poses a significant threat to Russia’s territorial integrity. It is clear that, despite differing interests, members of social communities should follow rules and norms based on compromises, mutual concessions, and principles of tolerance. However, practicing tolerance is challenging amid differing or clashing interests, ideas, traditions, preferences, and ambitions. Intolerance and xenophobia, the negative side of increasing religious and cultural diversity, hinder coexistence and make it more difficult to achieve. Pluralism and the actualization of differences multiply private interests, making it essential to find a common ground. In recent years, the problem of extremism in Russia has taken on new dimensions, with the threat of extremism in the regions becoming more apparent. Radicalization of society provides fertile ground for extremism to flourish. The state must focus on preventing extremism rooted in axiological shifts, the absence of a unifying ideology, social problems exacerbated by economic crises, corruption, a low cultural level, and various phobias (such as Russophobia and Islamophobia). The widening gap between the rich and poor, spiritual disorientation, and disagreements between religions and confessions also contribute to extremism. International extremist and terrorist organizations, which are spreading their criminal activities across the country, are particularly dangerous. Young people, who are often left to their own devices by their parents and society, are especially susceptible to radical ideas.